Psychological distress of first year medical students who underwent two different admission processes during a stressful period - Muhamad Saiful Bahri Yusoff,; Ahmad Fuad Abdul Rahim,; Abdul Aziz Baba,; Shaiful Bahari Ismail,; Hatta Sidi,; Ab Rahman Esa, (Universiti Kebangsaan Malaysia, 2013)
The study of medicine is often regarded by students as a stressful environment particularly during examination period. Studies found a high percentage of medical students experience significant psychological distress during the examination period. This study compared percentage and level of psychological distress between two batches of first year medical students who underwent different selection admission processes during a stressful examination period. A comparative cross-sectional study was done on two batches of first year medical students; one group selected based on academic merit (2008/2009 batch) and the other selected based on academic merit, psychometric tests and interview (2009/2010 batch). The psychological distress was measured by the 12-item general health questionnaire (GHQ-12). The data were collected right after the final examinations. A total of 99 (46.05%) medical students of the 2008/2009 batch and 196 (100%) medical students of the 2009/2010 batch participated. The percentage of medical students who had psychological distress of the 2008/2009 and the 2009/2010 batches were 58.59% and 42.3%, respectively. The mean GHQ-12 score and percentage of psychological distress were significantly different between the two batches (p< 0.01). The older batch had 2.01 times higher risk for developing psychological distress compared with the newer batch (p< 0.01). The newer batch of medical students had better psychological health status and was less likely to develop psychological distress during the stressful period compared with older batch.